The influence of photoperiodism in cucumbers growth and blossom - I. BARBAT; Eugenia POP (Notulae Botanicae Horti Agrobotanici Cluj-Napoca, 1970)
The experiment results show that the photoperiodism has a certain influence between the cucumbers male and female flowers.